(untitled) (Fiep Bulletin - online, 2013)
The objective of this study was to identify the profile of the physical qualities and dermatoglyphic indexes of Ruffoni Judo Team, from 9 to 14 years old. The study was performed by means of motive tests based on highly regarded protocols. The aim of this study is to evaluate the following physical qualities: dynamic equilibrium, motive co-ordination, agility and explosive strength. The group also went through an evaluation to identify the dermatoglyphic profile, by means of fingerprints. The sample was composed of 20 athletes of masculine gender who practice judo on Ruffoni Judo Team from 9 to 14 years old. The results found for physical qualities of the athletes from 9 to 11 years old were: Dynamic Equilibrium: 1,6 ± 0,52, Motor coordination: 3,90 ± 0,88, Agility: 12,18 ± 1,09 and Explosive Strength: 23,20 ± 3,19. The students from 12 to 14 years old presented the following values: Dynamic Equilibrium: 1,8 ± 0,42, Co-ordination: 4,10 ± 0,57, Agility: 11,07 ± 0,52 and Explosive Strength: 32,20 ± 7,28. The dermatoglyphic features found in the group from 9 to 11 years old were the following: Arc (A): 0,8 ± 1,1, Fastener (L): 7,9 ± 1,3, Verticilo (W): 1,3 ± 1,3, Delta Index (D10): 10,5 ± 2,1 and Summation of the Total Line Amount (SQTL): 123,1 ± 28,1. For the students of 12 to 14 years old, the following indexes were obtained: Arc (A): 1,4 ± 2,6, Fastener (L): 7,2 ± 2,4, Verticilo (W): 1,4 ± 1,3, Delta Index (D10): 10 ± 3,4, Summation of the Total Line Amount (SQTL): 96,4 ± 34,3. These results indicate that the students of Ruffoni Judo Team present a predisposition to physical qualities of speed and explosive strength, features that shall be explored in a way that they can have more chances of success in judo.